Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Loyalitas Pelanggan Pada Hotel Machudum Kota Padang - Agil Windya Zakirman; Fiko Farlis (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the effect of the marketing mix on customer loyalty at the Machudum Hotel in Padang City. The marketing mix studied includes seven elements, namely product, price, place, promotion, people, process, and physical evidence (7P). Customer loyalty is key to maintaining business existence, especially amidst the tight competition in the hotel industry in Padang City. This study uses a quantitative approach with a causal descriptive method. The research sample of 286 respondents was determined using the Slovin formula and selected using a purposive sampling technique, namely customers who have stayed at least twice in the past year at the Machudum Hotel. Data were collected through questionnaires and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4.0.9.1 software. The results showed that all elements of the marketing mix have a positive and significant influence on customer loyalty, both partially and simultaneously. This finding emphasizes the importance of an integrated marketing mix strategy oriented towards customer satisfaction to increase customer loyalty in the hotel sector.